Evaluating the efficiency of regional innovation systems in Europe: DEA approach - Łącka, Irena; Brzezicki, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
For many years, regional innovation systems in Europe have been studied and compared against each other within the framework of the Regional Innovation Scoreboard. However, it has a number of drawbacks, e.g. the combined input-output approach, which does not respond to societal expectations, as in this era of all-round economisation, it is the outputs of the activity that are more important than the potential contained in the inputs. Therefore, in our study we focused on an approach aimed at maximising the outputs achieved by regional innovation systems. The results of the study indicated that, even taking into account negative environmental outcomes, the vast majority of regional innovation systems show efficiency. We have shown that although the regional innovation systems group studied is highly efficient, our research indicates that in the long term, the narrow classification into four innovation groups according to the Regional Innovation Scoreboard methodology is increasingly less useful, as there is a reduction in the number of groups as a result of the ‘shift’ of units to three main ones. We also provided recommendations for EU regional innovation policy on the Regional Innovation Scoreboard tool. Our recommendation is to introduce more differentiated variables into the European survey and to focus more on evaluating the innovation system from the perspective of the results obtained and less on an input approach.

Od wielu lat regionalne systemy innowacji w Europie są badane i porównywane ze sobą w ramach Regional Innovation Scoreboard. Ma ona jednak szereg wad, np. podejście łączące nakłady i wyniki, które nie odpowiada oczekiwaniom społecznym, ponieważ w erze wszechstronnej ekonomizacji to wyniki działalności są ważniejsze niż potencjał zawarty w nakładach. Dlatego w naszym badaniu skupiliśmy się na podejściu mającym na celu maksymalizację wyników osiąganych przez regionalne systemy innowacji. Wyniki badania wskazały, że nawet biorąc pod uwagę negatywne skutki środowiskowe, zdecydowana większość regionalnych systemów innowacji wykazuje się efektywnością. Wykazaliśmy, że chociaż badana grupa regionalnych systemów innowacji jest wysoce wydajna, nasze badania wskazują, że w dłuższej perspektywie wąska klasyfikacja na cztery grupy innowacji zgodnie z metodologią Regional Innovation Scoreboard jest coraz mniej użyteczna, ponieważ następuje zmniejszenie liczby grup w wyniku „przesunięcia” jednostek do trzech głównych. Przedstawiliśmy również zalecenia dla regionalnej polityki innowacji UE dotyczące narzędzia Regional Innovation Scoreboard. Naszym zaleceniem jest wprowadzenie bardziej zróżnicowanych zmiennych do europejskiego badania i skupienie się bardziej na ocenie systemu innowacji z perspektywy uzyskanych wyników, a mniej na podejściu wejściowym.
Ocena efektywności regionalnych systemów innowacji w Europie: podejście DEA
Keywords: regional innovation systems; efficiency; Europe; DEA; regionalne systemy innowacyjne; efektywność; Europa